An Early Diagnosis of Gastroepiploic Arterial Aneurysm during a Routine Abdominal Ultrasound Study - Giovanni Casella; Adriana Sartirana; Pietro Vandoni; Camillo Di Bella; Fabio Pagni; Paolo Nobili (Case Reports in Gastrointestinal Medicine)
Gastroepiploic arterial aneurysm (GEAA) is a rare condition, but the rupture risk is very high. We report the case of a patient with incidental finding of GEAA during US examination. The diagnosis was confirmed by a computed tomography and an angiographic study. A classic laparotomy with aneurysmectomy has been successfully performed.